Solar flare rates and probabilities based on the McIntosh classification: Impacts of GOES/XRS rescaling and revisited sunspot classifications - Janssens Jan; Delouille Véronique; Clette Frédéric; Andries Jesse (Journal of Space Weather and Space Climate)
In December 2019, the Space Weather Prediction Center (SWPC) started using the GOES1-16 satellite as its primary input for solar X-ray flux monitoring. As such, it stopped applying a scaling factor that had been applied since the GOES-8 came into operation. This has an important impact on the number of flares that can be expected and on the flare rates associated with the McIntosh classifications, which are often used to help forecast flare activity. To quantify the effects, the flare intensities for the period covering 1976–2019 have all been recalculated. An increase of respectively 55% and 52% in the total number of M-class and X-class events has been observed. Also, for the same period, McIntosh classifications have been redone by visually evaluating 4720 Kanzelhöhe solar drawings (about 1 drawing every 3 days) and determining the McIntosh type of 22232 sunspot regions. There is an excellent agreement with the values originally reported by McIntosh (1990), but some deviations from the SWPC data are found. For a majority of the McIntosh classes, an increase in the flare rates is observed, which translates into increased flare probabilities assuming a Poisson distribution for the flare occurrence. This is an important given for space weather forecasters when making solar flare forecasts. The McIntosh classification is successful in distinguishing flare active from flare inactive regions: Considering only the “p” and “c” components of the McIntosh classification and linking them to the number of flares associated with the corresponding sunspot groups, we find that 48% of all M- and X-class flares in our study are produced by only 8% of all sunspot groups, belonging to the McIntosh subclasses -ai, -kc, and -ki corresponding to sunspot groups with an asymmetric main spot and a more complex (intermediate or compact) internal sunspot distribution. About 57% of all classified sunspot groups produce only 12% of all M- and X-class flares. They belong to the McIntosh subclasses -so, -sx, -xo, and -xx, which correspond to the smallest and simplest sunspot regions and the phases marking the emergence and final decay of sunspot groups (Axx, Bxo, Hsx). Though the McIntosh classification is a great tool to forecast flare activity, there remain large differences in the actual flare behaviour of individual sunspot groups within the same McIntosh class.